The Hubungan Kepatuhan Minum Obat Dengan Kecemasan Dan Kualitas Hidup Pasien TB Paru - Nazmi, Annisa Nur; Toga, Ervia; Firdaus (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: This study aims to determine the relationship between medication adherence and anxiety and quality of life of Pulmonary TB patients Methods: This study used was cross-sectional. The research sample was Pulmonary TB patients at the Pulmonary Polyclinic of PKU Muhammadiyah Rogojampi Hospital, Banyuwangi Regency, with 42 respondents. The sampling technique used was total sampling. Data collection used a questionnaire with the Spearman Rank test. The questionnaires used were the Morisksy Medication Adherence Scale (MMAS-8), HARS (Hamilton Anxiety Rating Scale), and World Health Organization Quality of Life- Bref (WHOQOL-BREF) Results: Almost half of the medication compliance 18 respondents (42.9%), almost half of the anxiety 18 respondents (42.9%), almost half of the quality of life 16 respondents (38.1%), there is a relationship between medication compliance and anxiety with a significant value (sig. 2-tailed) 0.00 (<0,05), there is a relationship between medication compliance and quality of life with a significant value (sig. 2 tailed) 0.00 (<0,05). So, it can be concluded that medication compliance with anxiety is related to quality of life. Conclusion: Respondents are expected to be able to consume medication regularly so that treatment can run optimally, decreasing anxiety and improving quality of life.